2015
DOI: 10.20452/pamw.2888
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of iron deficiency anemia: practical considerations

Abstract: The aims of this article, which is directed primarily at generalists, are to outline the relevant features of iron metabolism, to summarize the indications for treatment of IDA, and to compare the advantages and disadvantages of treatment with oral and intravenous iron. We shall then focus particularly on practical aspects of treatment with iron. Topics which we shall not cover include investigation of the cause of IDA (for guidance, see Goddard et al 3 ) and use of blood transfusion. We shall also omit the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
0
8
0
2
Order By: Relevance
“…[ 5 ] Compromised iron stores cause adaptive changes, eventually resulting in limitations to the production of hemoglobin and a state of IDA. Menstruation is the most common single cause of IDA in females of a childbearing age,[ 6 ] with HMB specifically identified as the principal cause of iron deficiency and IDA in clinical practice in this population. [ 7 ] In a recent study of women with HMB, 63% of respondents reported being deficient in iron at some point.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] Compromised iron stores cause adaptive changes, eventually resulting in limitations to the production of hemoglobin and a state of IDA. Menstruation is the most common single cause of IDA in females of a childbearing age,[ 6 ] with HMB specifically identified as the principal cause of iron deficiency and IDA in clinical practice in this population. [ 7 ] In a recent study of women with HMB, 63% of respondents reported being deficient in iron at some point.…”
Section: Introductionmentioning
confidence: 99%
“…Our present findings suggest that even if superovulation treatment is used for patients with IDA, their fertility is not likely to improve. In humans, IDA can be treated with oral iron supplements [ 31 ]. The LFD-fed mice in this study that were later given the normal diet recovered from the effects of iron deficiency, including a return to the normal estrous cycle and fertility.…”
Section: Discussionmentioning
confidence: 99%
“…4 This is the first study to analyze the treatment pattern in patients having IDA. In our study, majority of the patients were female (71%) and they were more than 15 years of age.…”
Section: Discussionmentioning
confidence: 99%